Influence of desalination concentrate medium on microalgal metabolism, biomass production and biochemical composition - Matos, Ângelo Paggi [UNESP]; Saldanha-Corrêa, Flávia Marisa Prado; Hurtado, Gabriela Ramos [UNESP]; Vadiveloo, Ashiwin; Moheimani, Navid Reza (Wiley, 2024)
Reverse osmosis is currently the most promising method for addressing freshwater scarcity in numerous nations, enabling the production of drinkable water for human consumption. This process, however, generates a byproduct stream, known as desalination concentrate (DC), that is enriched with high concentrations of salts such as Na+ and Cl−, moderate levels of SO42−, Mg2+, Ca2+ and K+ and trace levels of Si, Fe3+, NO3− and PO43−, which can be suitable and valuable for microalgal metabolism and growth. Salt concentration in DC can significantly influence microalgal growth via effects through osmotic shock, salt stress and cellular ionic ratios. Under certain conditions, these salinity changes can have a positive impact on microalgal metabolism, such as the synthesis of lipophilic compounds that include lipids, fatty acids and carotenoids. This mini-review aims to provide up-to-date information of recent studies conducted towards the use of DC as a potential substrate for microalgal cultivation as well as to summarize the response mechanism of microalgae when cultured in DC. Several laboratory-based studies have examined the effect of different DC concentrations on the biochemical composition of microalgae grown either in photobioreactors or in raceway ponds. These studies have uncovered significant effects of DC on the synthesis of proteins, amino acids and phycocyanin in freshwater species like Chlorella vulgaris and Arthrospira platensis, where DC tends to hinder these processes. Conversely, experiments with halophilic Dunaliella salina and marine Nannochloropsis gaditana have demonstrated that increasing DC concentration can positively influence the production of β-carotene, lipids and specific saturated fatty acids (C16:0 and C18:0), suggesting that these species can adapt to a broader range of DC salinities. Cultivating salinity-tolerant microalgae in DC would greatly reduce the production cost of algal-based products, offering a promising approach to enhance the profitability of desalination and microalgal industries. © 2023 Society of Chemical Industry (SCI).
Keywords: algal cultivation; biochemical alterations; desalination wastewater; lipids; salt concentration